2017
DOI: 10.2485/jhtb.26.51
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Chemically Synthesized Leucine-Rich Amelogenin Peptide (csLRAP) on Chondrogenic and Osteogenic Cells

Abstract: Amelogenin is one of the enamel matrices secreted by ameloblasts and is known to have at least 15 alternative mRNA splicing isoforms. The leucine rich amelogenin peptide (LRAP) is one of most abundant amelogenin isoforms and numerous studies have shown that amelogenin peptides including LRAP, are expressed in cartilage and bone. Lysosome-associated membrane protein-1 (LAMP-1) has been identified as amelogenin binding partner, however, the mechanism of action for LRAP in chondrogenesis or osteogenesis is still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Of the latter, 10 [24][25][26][27][28][29][30][31][32][33] were excluded due to the descriptive analysis (Table 1), while 14 studies met the inclusion criteria (Table 2). In the 14 studies selected [8,[34][35][36][37][38][39][40][41][42][43][44][45][46], it was not possible to perform a quantitative analysis due to major differences in terms of the cell model, peptide concentrations, time points, and methodologies employed (Table 2). Among the included papers, there were no clinical trials, 13 were in vitro [8,[34][35][36][37][38][39][41][42][43][44][45][46], and 1 was in vivo [40].…”
Section: Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the latter, 10 [24][25][26][27][28][29][30][31][32][33] were excluded due to the descriptive analysis (Table 1), while 14 studies met the inclusion criteria (Table 2). In the 14 studies selected [8,[34][35][36][37][38][39][40][41][42][43][44][45][46], it was not possible to perform a quantitative analysis due to major differences in terms of the cell model, peptide concentrations, time points, and methodologies employed (Table 2). Among the included papers, there were no clinical trials, 13 were in vitro [8,[34][35][36][37][38][39][41][42][43][44][45][46], and 1 was in vivo [40].…”
Section: Systematic Reviewmentioning
confidence: 99%
“…In the 14 studies selected [8,[34][35][36][37][38][39][40][41][42][43][44][45][46], it was not possible to perform a quantitative analysis due to major differences in terms of the cell model, peptide concentrations, time points, and methodologies employed (Table 2). Among the included papers, there were no clinical trials, 13 were in vitro [8,[34][35][36][37][38][39][41][42][43][44][45][46], and 1 was in vivo [40]. Only one article tested TRAP [38], five LRAP [8,[34][35][36][37], six SP [39][40][41][42][43][44], and two the C11 peptide [45,46].…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…7). It has been suggested that LAMP-1 and LAMP-3 on the cell membrane bind to amelogenin and could be signaling receptor of amelogenin (Veis et al, 2000;Zou et al), and several studies have shown that LAMP-1 and LAMP-3 may be involved in the biological function of amelogenin as signaling molecules (Xu et al, 2008;Zhang et al, 2010;Kunimatsu et al, 2011;Matsuda et al, 2017). The cytoplasm of the secretory stage Amelx* ameloblasts has been reported to display strong amelogenin immunopositivity (Barron et al).…”
Section: Discussionmentioning
confidence: 99%
“…A proportional number of cells was counted, as described previously [17] with minor modification. Briefly, HAM2 cells were seeded at each cell density, 5.0, 2.5, and 0.6 × 10 3 cells per well on a type I collagen-coated 96-well plate (Corning Life Sciences, NY, USA) depending on each experiment.…”
Section: Cell Proliferationmentioning
confidence: 99%